Method for deep removal of impurity iron from recycled aluminum-silicon alloy material, and purified aluminum-silicon alloy

CN122979654APending Publication Date: 2026-10-27CENT SOUTH UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611111028.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]旨在解决上述常用技术中如何在无需复杂设备和高能耗的条件下,针对性处理铁含量≤1.0wt.%的再生铝硅合金中尺寸超过50μm的细长针状β-Fe相,实现铁的深度去除的技术问题,本发明提供了一种深度去除低铁再生铝硅合金材料中杂质铁的方法,包括以下步骤:

Benefits of technology

本发明首先将低铁再生铝硅合金与含锰化合物混合熔融,向合金熔体中引入锰元素。锰能够将原料中原本有害的细长针状β铁相转变为块状或颗粒状的α-Fe相(富铁相),这一变质处理一方面消除了针状相对铝合金基体的割裂危害,另一方面,块状相比针状相在熔体中具有更好的流动性和聚集性,更易于在后续工序中迁移和富集。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979654A_ABST
    Figure CN122979654A_ABST
Patent Text Reader

Abstract

The present application belongs to the field of impurity removal of recycled aluminum, and particularly relates to a method for deeply removing impurity iron in low-iron recycled aluminum silicon alloy material and a pure aluminum silicon alloy. The method comprises the following steps: adding a manganese-containing compound to modify the needle-shaped iron-rich phase, adding metal zinc to form an aluminum-zinc melt, using the ultra-low solubility of zinc to iron and the high-density melt characteristics to make the iron-rich phase float to the surface layer at 570 DEG C to 620 DEG C, cutting off the top iron-rich layer after cooling and solidification, and separating zinc from the bottom low-iron aluminum-zinc alloy through vacuum distillation to obtain the pure aluminum silicon alloy after iron removal, and the recycled zinc can be recycled.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of recycled aluminum impurity removal technology, specifically relating to a method for deep removal of impurity iron from low-iron recycled aluminum-silicon alloy materials, and a pure aluminum-silicon alloy. Background Technology

[0002] The recycled aluminum industry is an important way to alleviate bauxite resource shortages and reduce the high energy consumption and emissions of electrolytic aluminum. The unit energy consumption of recycled aluminum production is only 3% to 5% of that of primary aluminum, resulting in a significant reduction in carbon emissions. However, the preservation and upgrading of recycled aluminum has long been constrained by the effective removal of iron impurities. Iron is the most significant harmful impurity element in recycled aluminum. Due to the complex sources of waste aluminum and the high difficulty of pretreatment, a large amount of iron impurities are inevitably mixed in during the recycling process. During the solidification of aluminum-silicon alloys, iron forms a hard and brittle needle-like β-Fe phase with aluminum and silicon. This phase can fracture the aluminum alloy matrix, reducing the alloy's plasticity, strength, and corrosion resistance, forcing the recycled aluminum to be downgraded for reuse.

[0003] Currently, the mainstream methods for iron removal in recycled aluminum include gravity sedimentation, centrifugal removal, filtration, electromagnetic separation, and fluxing. Each of these methods has inherent technical drawbacks: gravity sedimentation transforms the needle-like β-Fe phase into a high-melting-point primary α-Fe phase by adding elements such as manganese, allowing it to settle to the bottom of the crucible due to density differences. However, this method requires a long settling time. More importantly, when the iron content is low (≤1.0 wt.%), the iron phase is scarce and slender, with a very small equivalent radius. According to Stokes' law, the settling efficiency decreases sharply with the square of the particle radius, making it difficult to completely separate the iron phase from the aluminum melt, resulting in poor iron removal. While centrifugal removal and electromagnetic separation can enhance the separation effect, they require high equipment investment, consume a lot of energy, and are difficult to scale up for continuous production. Electromagnetic separation also requires a significant difference in conductivity between the iron phase and the melt. For fine needle-like iron phases, their high aspect ratio makes them prone to rotation or oscillation during melt flow, resulting in complex magnetization directions, uneven local stress, and poor separation stability. The filtration method uses foam ceramic filter plates to intercept iron-rich particles, but needle-shaped iron phases are prone to bending and deformation, penetrating the filter plates (especially when the length direction is aligned with the filter holes), resulting in low filtration efficiency and severe filter plate clogging, making continuous operation difficult. Although the flux method is simple to operate, the iron removal rate is generally low (usually <60%), and it is prone to introducing secondary pollution.

[0004] In summary, existing technologies, while achieving low cost and low energy consumption, struggle to achieve deep iron removal (reducing to below 0.12 wt.%) from recycled aluminum-silicon alloys with low iron content (≤1.0 wt.%), severely hindering the preservation and upgrading of recycled aluminum-silicon alloy materials. Therefore, there is an urgent need to develop a new method that requires no complex equipment, consumes low energy, and can deeply remove impurities of iron from recycled aluminum-silicon alloys with low iron content without introducing secondary pollution. Summary of the Invention

[0005] Aiming to solve the technical problem of how to achieve deep removal of slender needle-like β-Fe phases with a size exceeding 50 μm in recycled aluminum-silicon alloys with an iron content ≤1.0 wt.% without complex equipment and high energy consumption, this invention provides a method for deep removal of impurity iron from low-iron recycled aluminum-silicon alloy materials, comprising the following steps: Low-iron recycled aluminum-silicon alloy is mixed and melted with manganese-containing compounds to obtain a mixed aluminum melt; Add metallic zinc to the mixed aluminum melt to form an aluminum-zinc melt; The aluminum-zinc melt is cooled to 570℃~620℃ and held for heat treatment to allow the iron-rich phase to float to the surface of the melt. Then, the melt is cooled to solidify and obtain aluminum ingots. The lower part of the aluminum ingot is taken and subjected to vacuum zinc volatilization-condensation separation to obtain a pure aluminum-silicon alloy.

[0006] Furthermore, in the mixed aluminum melt, the molar ratio of manganese to iron is (1~3):1; In the aluminum-zinc melt, the mass ratio of the mixed aluminum melt to metallic zinc is 3:(3~7).

[0007] Furthermore, in the low-iron recycled aluminum-silicon alloy, the silicon content is 4~12 wt.% and the iron content is 0.15~1.0 wt.%.

[0008] Furthermore, the manganese-containing compound includes an aluminum-manganese master alloy; the mass percentage of manganese in the aluminum-manganese master alloy is 10-20%.

[0009] Furthermore, the melting temperature of the low-iron recycled aluminum-silicon alloy mixed with the manganese-containing compound is ≥700℃; The temperature at which zinc is added to the mixed aluminum melt for melting is 630~700℃.

[0010] Furthermore, the method of cooling the aluminum-zinc melt to 570°C~620°C includes slow cooling at a rate of 50~100°C / h; The heat preservation treatment lasts for 30 to 180 minutes; before the heat preservation treatment, a stirring treatment is also included, which lasts for 15 to 20 minutes.

[0011] Furthermore, the cooling process includes rapid cooling with a cooling rate of ≥150℃ / h.

[0012] Furthermore, the method of removing the lower part of the aluminum ingot is as follows: the top area of ​​the aluminum ingot is removed, and the remaining area is subjected to vacuum zinc volatilization-condensation separation; the top area accounts for more than 10% of the total height of the aluminum ingot.

[0013] Furthermore, the conditions for the vacuum zinc volatilization-condensation separation are as follows: the reaction zone temperature is 880~920℃, the reaction zone is evacuated to a vacuum state before heating, and the distillation separation time after the reaction zone reaches 880~920℃ is 1.5~4h.

[0014] This invention provides a pure aluminum-silicon alloy with deep iron impurity removal, prepared by the method described above. In this pure aluminum-silicon alloy, the iron content is less than 0.12 wt.% and the zinc content is less than 0.01 wt.%. In the pure aluminum-silicon alloy, the iron phase is in the form of non-needle-shaped blocks or granules, and the maximum size of the iron phase is ≤30μm.

[0015] Compared with the prior art, the present invention has at least the following advantages: This invention first involves mixing and melting a low-iron recycled aluminum-silicon alloy with a manganese-containing compound, introducing manganese into the alloy melt. Manganese can transform the originally harmful elongated needle-like β-iron phase in the raw material into a blocky or granular α-Fe phase (iron-rich phase). This modification treatment eliminates the cutting hazard of the needle-like phase on the aluminum alloy matrix. Furthermore, the blocky phase has better fluidity and aggregation in the melt than the needle-like phase, making it easier to migrate and accumulate in subsequent processes.

[0016] The experimental results of Comparative Example 1 verified this effect: without the addition of manganese, the iron phase in the melt was still mainly acicular β-Fe, and the flotation effect was significantly worse. The iron content at position 1 at the top was only 0.15%, which was lower than the 0.38% at position 2. The iron phase failed to be effectively enriched on the surface.

[0017] This invention involves adding metallic zinc to a mixed aluminum melt to form an aluminum-zinc melt. This step has dual technical benefits. On the one hand, zinc has extremely low solubility for iron. The addition of zinc alters the original physicochemical equilibrium of the aluminum melt, breaking the binding effect of the aluminum melt on iron atoms and forcing iron to precipitate from the aluminum melt in solid form. On the other hand, the density of the aluminum-zinc melt is significantly higher than that of pure aluminum melt, providing a high-density bottom liquid phase environment for the migration of the iron-rich phase, greatly reducing the resistance encountered by the iron-rich phase during its upward movement.

[0018] The experimental results of Comparative Example 2 fully demonstrate the key role of zinc: without the addition of zinc, aluminum-zinc melt cannot be formed, the iron content in different parts at different heights is not significantly different (all are about 0.3 wt.%), and the iron phase cannot achieve flotation and separation.

[0019] This invention involves cooling the aluminum-zinc melt to 570℃~620℃ and holding it within this temperature range. This temperature is lower than the conventional aluminum-silicon alloy melting temperature, allowing the iron-rich phase to fully precipitate in a supersaturated state while the aluminum-zinc melt maintains good fluidity. Combined with the high density of the aluminum-zinc melt, the precipitated iron-rich phase spontaneously migrates and accumulates towards the melt surface under gravity, forming an iron-rich layer (slag) with a significantly higher iron content than the average level of the melt. Experimental data shows that after this treatment, the iron content at position 1 on the melt surface can reach 0.53%~0.71%, while the iron content at position 6 at the bottom can be as low as 0.03%~0.08% (Examples 1~3 in Table 1), showing a significant gradient distribution of iron content between the upper and lower parts, confirming that the iron-rich phase has achieved efficient flotation. Compared with the traditional gravity settling method, this invention transforms the sinking approach into a floating approach, avoiding the small equivalent radius and slow settling speed of the acicular iron phase (Stokes' Law: v∝r). 2 The physical bottleneck.

[0020] This invention utilizes vacuum zinc volatilization-condensation separation of the lower part of the processed aluminum ingot, achieving two key technical advantages. First, by cutting and removing the lower aluminum ingot, the iron-rich layer (top) and the low-iron aluminum-zinc alloy (bottom) are physically separated, removing most iron impurities from the system. Second, vacuum distillation leverages the significant difference in vapor pressure between aluminum and zinc at the same temperature—zinc's vapor pressure is much higher than aluminum's—causing zinc in the aluminum-zinc melt to volatilize into the gas phase and be recovered in the condensation zone, while aluminum remains in the quartz boat. Experimental data (Table 2) show that after vacuum distillation, the zinc content in the pure aluminum-silicon alloy can be reduced to 0.0010%~0.0045 wt.%, far below the industrial application control target of 0.01 wt.%. Attached Figure Description

[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0022] Figure 1 These are scanning electron microscope (SEM) comparison images of alloy ingots of different heights obtained after melt treatment in Examples 1-5 of the present invention.

[0023] Figure 2 The images shown are scanning electron microscope (SEM) images of the pure aluminum-silicon alloys obtained after vacuum zinc volatilization-condensation separation in Examples 6-7 of this invention.

[0024] Figure 3These are scanning electron microscope (SEM) comparison images of alloy ingots of different heights obtained after melt treatment in Comparative Examples 1-2 of this invention. Detailed Implementation

[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0027] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention, as well as the prior art known to those skilled in the art and the description of the invention, may be implemented using any prior art methods, devices, and materials similar to or equivalent to the methods, devices, and materials in the embodiments of the present invention.

[0028] This invention provides a method for deep removal of iron impurities from low-iron recycled aluminum-silicon alloy materials, comprising the following steps: S1. Mix and melt low-iron recycled aluminum-silicon alloy with manganese-containing compounds to obtain a mixed aluminum melt.

[0029] In some embodiments, the molar ratio of manganese to iron in the mixed aluminum melt is (1~3):1.

[0030] In some embodiments, the low-iron recycled aluminum-silicon alloy contains 4-12 wt.% silicon and 0.15-1.0 wt.% iron.

[0031] In some embodiments, the manganese-containing compound comprises an aluminum-manganese master alloy; the mass percentage of manganese in the aluminum-manganese master alloy is 10-20%. Since an aluminum-manganese master alloy content below 10% introduces excessive aluminum during batching, it is inconvenient; an aluminum-manganese master alloy content above 20% has a high melting point and is difficult to melt at the melting temperature of this invention; the mass percentage of manganese in the aluminum-manganese master alloy can be 10%, 11%, 13%, 15%, 20%, or any other value within the range of 10% to 20%. Preferably, the aluminum-manganese master alloy is Al-10Mn (an aluminum-manganese master alloy with a manganese mass percentage of 10%).

[0032] In some embodiments, the temperature at which the low-iron recycled aluminum-silicon alloy is mixed and melted with the manganese-containing compound is ≥700°C.

[0033] More specifically, the melting temperature of the low-iron recycled aluminum-silicon alloy and the manganese-containing compound can be 700~1100℃, such as 700~1000℃.

[0034] S2. Add metallic zinc to the mixed aluminum melt to form an aluminum-zinc melt.

[0035] In some embodiments, the mass ratio of the mixed aluminum melt to metallic zinc in the aluminum-zinc melt is 3:(3~7).

[0036] In some embodiments, the temperature at which metallic zinc is added to the mixed aluminum melt for melting is 630~700°C. Melting at this temperature allows the aluminum and zinc melts to become fully miscible, facilitating the subsequent breaking of the binding effect of the aluminum melt on the iron-rich phase by the aluminum melt.

[0037] More specifically, the temperature at which zinc is added to the mixed aluminum melt for melting can be 640~660℃.

[0038] S3. The aluminum-zinc melt is cooled to 570℃~620℃ and held for heat treatment, causing the iron-rich phase to float to the surface of the melt. Then, it is cooled down to solidify the melt into an aluminum ingot. Holding the melt at this temperature allows the iron-rich phase to precipitate at low temperatures and float to the top of the melt in a high-density state, forming slag.

[0039] In some embodiments, cooling the aluminum-zinc melt to 570°C to 620°C includes slow cooling at a rate of 50 to 100°C / h.

[0040] In some embodiments, the heat preservation treatment lasts for 30 to 180 minutes; before the heat preservation treatment, a stirring treatment is also included, which lasts for 15 to 20 minutes.

[0041] In some embodiments, the cooling process includes rapid cooling at a rate of ≥150°C / h. Rapid cooling causes the melt temperature to drop rapidly, and the melt immediately solidifies, preventing the iron-rich phase from diffusing to the surrounding area, thereby fixing the iron-rich phase at the top of the melt.

[0042] More specifically, the final temperature of the cooling process is 10~30℃; for example, the final temperature of the cooling process can be room temperature.

[0043] S4. Take the lower part of the aluminum ingot and perform vacuum zinc volatilization-condensation separation to obtain a pure aluminum-silicon alloy.

[0044] In some embodiments, the method of removing the lower part of the aluminum ingot is as follows: the top region of the aluminum ingot is removed, and the remaining region is subjected to vacuum zinc volatilization-condensation separation. That is, the lower part is the remaining region after removing the top region.

[0045] In some embodiments, the top region may account for more than 10% of the total height of the aluminum ingot.

[0046] More specifically, the top region may account for 10-25% of the total height of the aluminum ingot, such as 10%-15%, 10%-18%, 10%-20%, 10%-25%, 15-20%, 15-25%, or 15%-30%.

[0047] In some embodiments, the conditions for vacuum zinc volatilization-condensation separation are: the reaction zone temperature is 880~920℃, the reaction zone is evacuated to a vacuum state before heating, and the distillation separation time after the reaction zone reaches 880~920℃ is 1.5~4h.

[0048] More specifically, the condensation zone may not require heating, meaning the temperature of the condensation zone can be room temperature.

[0049] At temperatures of 880-920℃, zinc in the molten aluminum-zinc mixture volatilizes, while aluminum remains inside the quartz boat, thus achieving aluminum-zinc separation. The condensation zone, without a set temperature, allows the volatilized zinc to re-condense onto the tube wall for subsequent zinc recovery.

[0050] The present invention also provides a pure aluminum-silicon alloy with deep removal of impurity iron, which is prepared by the method described above. In the pure aluminum-silicon alloy, the iron content is less than 0.12 wt.% and the zinc content is less than 0.01 wt.%.

[0051] In some embodiments, the iron phase in the pure aluminum-silicon alloy is in the form of non-needle-shaped blocks or granules, and the maximum size of the iron phase is ≤30μm.

[0052] To facilitate a further understanding of the present invention by those skilled in the art, the following examples are provided: Example 1 Ingredients: Mix 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn to adjust the composition. The mass ratio of aluminum to silicon to manganese to iron is 92.15:7:0.55:0.3; the molar ratio of manganese to iron is 1.83:1.

[0053] S1. Dry 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly to obtain a mixed aluminum melt.

[0054] The 192g aluminum-silicon alloy and 3.6g Al-10Fe together constitute a low-iron recycled aluminum-silicon alloy material, and the 12g Al-10Mn is a manganese-containing compound.

[0055] Specifically, the 192g aluminum-silicon alloy contains approximately 6.87 wt.% silicon and approximately 0.18 wt.% iron. 12g Al-10Mn, as a manganese-containing compound, is mixed and melted with the aforementioned low-iron recycled aluminum-silicon alloy.

[0056] S2. Adjust the temperature of the mixed aluminum melt to 650℃, then add 311.4g of metallic zinc to the mixed aluminum melt, melt it again and stir for 5min to obtain a uniform aluminum-zinc melt; wherein, the mass ratio of mixed aluminum melt to metallic zinc in the mixed aluminum-zinc melt is 4:6.

[0057] S3. Adjust the temperature of the aluminum-zinc melt to 580℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed aluminum-zinc melt is consistent. Then, hold at 580℃ for 1 hour, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0058] Example 2 Ingredients: Mix 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn to adjust the composition. The mass ratio of aluminum to silicon to manganese to iron is 92.15:7:0.55:0.3; the molar ratio of manganese to iron is 1.83:1.

[0059] S1. Dry 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly to obtain a mixed aluminum melt.

[0060] S2. Adjust the temperature of the mixed aluminum melt to 650℃, then add 311.4g of metallic zinc to the mixed aluminum melt, melt it again and stir for 5min to obtain a uniform aluminum-zinc melt; wherein, the mass ratio of mixed aluminum melt to metallic zinc in the mixed aluminum-zinc melt is 4:6.

[0061] S3. Adjust the temperature of the mixed aluminum-zinc melt to 580℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed aluminum-zinc melt is consistent. Then, hold at 580℃ for 3 hours, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0062] Example 3 Ingredients: Mix 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn to adjust the composition. The mass ratio of aluminum to silicon to manganese to iron is 92.15:7:0.55:0.3; the molar ratio of manganese to iron is 1.83:1.

[0063] S1. Dry 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat it until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly.

[0064] S2. Adjust the temperature of the mixed aluminum melt to 650℃, then add 311.4g of metallic zinc to the mixed aluminum melt, melt it again and stir for 5min to obtain a uniform aluminum-zinc melt; wherein, the mass ratio of mixed aluminum melt to metallic zinc in the mixed aluminum-zinc melt is 4:6.

[0065] S3. Adjust the temperature of the mixed aluminum-zinc melt to 600℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed aluminum-zinc melt is consistent. Then, hold at 600℃ for 1 hour, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0066] Example 4 Ingredients: Mix 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn to adjust the composition. The mass ratio of aluminum to silicon to manganese to iron is 92.15:7:0.55:0.3; the molar ratio of manganese to iron is 1.83:1.

[0067] S1. Dry 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat it until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly to obtain a mixed aluminum melt.

[0068] S2. Adjust the temperature of the mixed aluminum melt to 650℃, then add 138.1g of metallic zinc to the mixed aluminum melt, melt it again and stir for 5min to obtain a uniform aluminum-zinc mixed melt; wherein, the mass ratio of mixed aluminum melt to metallic zinc in the mixed aluminum-zinc melt is 6:4.

[0069] S3. Adjust the temperature of the mixed aluminum-zinc melt to 600℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed aluminum-zinc melt is consistent. Then, hold at 600℃ for 1 hour, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0070] As can be seen from the data in Table 1, the iron content at position 6 (bottom) in Example 4 is as high as 0.29%, significantly higher than the bottom iron content in Examples 1-3 and 5 (0.03%, 0.02%, 0.08%, and 0.03%, respectively), and even roughly equivalent to that in Comparative Example 2 (without zinc addition, bottom Fe content 0.31%). This demonstrates that when the zinc content is insufficient, the density of the aluminum-zinc mixed melt is inadequate, the driving force for the upward movement of the iron-rich phase weakens, and a large amount of iron cannot effectively float and remains in the bottom alloy, resulting in a significantly worse iron removal effect. This proves that the aluminum-zinc ratio is a key parameter affecting the efficient upward movement of the iron-rich phase, further illustrating the necessity of limiting this mass ratio to the range of 3:3 to 3:7.

[0071] Example 5 Ingredients: Mix 189g of aluminum-silicon alloy, 3.45g of Al-10Fe, and 6.3g of Al-10Mn to adjust the composition. The mass ratio of aluminum to silicon to manganese to iron is 92.4:7:0.3:0.3, and the molar ratio of manganese to iron is 1.86:1.

[0072] S1. Dry 189g of aluminum-silicon alloy, 3.45g of Al-10Fe, and 6.3g of Al-10Mn. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat it until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly.

[0073] S2. Adjust the temperature of the mixed aluminum melt to 650℃, then add 297.4g of metallic zinc to the mixed aluminum melt, melt it again and stir for 5min to obtain a uniform aluminum-zinc melt; wherein, the mass ratio of mixed aluminum melt to metallic zinc in the mixed aluminum-zinc melt is 4:6.

[0074] S3. Adjust the temperature of the mixed aluminum-zinc melt to 600℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed aluminum-zinc melt is consistent. Then, hold at 600℃ for 1 hour, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0075] Example 6 Ingredients: Mix 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn to adjust the composition. The mass ratio of aluminum to silicon to manganese to iron is 92.15:7:0.55:0.3; the molar ratio of manganese to iron is 1.83:1.

[0076] S1. Dry 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat it until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly.

[0077] S2. Adjust the temperature of the mixed aluminum melt to 650℃, then add 311.4g of metallic zinc to the mixed aluminum melt, melt it again and stir for 5min to obtain a uniform aluminum-zinc melt; wherein, the mass ratio of mixed aluminum melt to metallic zinc in the mixed aluminum-zinc melt is 4:6.

[0078] S3. Adjust the temperature of the mixed aluminum-zinc melt to 580℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed aluminum-zinc melt is consistent. Then, hold at 580℃ for 1 hour, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0079] S4. Take a certain amount of upper aluminum ingot and lower aluminum ingot, with the upper aluminum ingot accounting for 1 / 6 of the total volume of the aluminum ingot and the lower aluminum ingot accounting for 5 / 6 of the total volume of the aluminum ingot. Place them in a quartz boat and put them in a tube furnace for vacuum zinc volatilization-condensation separation. The reaction zone temperature is 900℃ and the vacuum distillation time is 2h. After zinc volatilization and condensation, pure aluminum-silicon alloy is obtained.

[0080] Example 7 Ingredients: Mix 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn to adjust the composition. The mass ratio of aluminum to silicon to manganese to iron is 92.15:7:0.55:0.3; the molar ratio of manganese to iron is 1.83:1.

[0081] S1. Dry 192g of aluminum-silicon alloy, 3.6g of Al-10Fe, and 12g of Al-10Mn. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat it until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly.

[0082] S2. Adjust the temperature of the mixed aluminum melt to 650℃, then add 311.4g of metallic zinc to the mixed aluminum melt, melt it again and stir for 5min to obtain a uniform aluminum-zinc melt; wherein, the mass ratio of mixed aluminum melt to metallic zinc in the mixed aluminum-zinc melt is 4:6.

[0083] S3. Adjust the temperature of the mixed aluminum-zinc melt to 580℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed aluminum-zinc melt is consistent. Then, hold at 580℃ for 1 hour, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0084] S4. Take a certain amount of the upper aluminum ingot and the lower aluminum ingot after processing, wherein the volume of the upper aluminum ingot accounts for 1 / 6 of the total volume of the aluminum ingot and the volume of the lower aluminum ingot accounts for 5 / 6 of the total volume of the aluminum ingot. Place them in a quartz boat and put them in a tube furnace for vacuum zinc volatilization-condensation separation. The reaction zone temperature is 900℃ and the vacuum distillation time is 3h. After zinc volatilization and condensation, pure aluminum-silicon alloy is obtained.

[0085] Analysis example 1 Samples (1-6) were taken sequentially from top to bottom of the alloy ingots in Examples 1 to 5 at equal intervals, and the Fe content was tested. The results are compared in Table 1. Scanning electron microscopy (SEM) was used to observe the top and bottom samples of the alloy ingots in Examples 1-5. Figure 1 As shown.

[0086] Table 1. Comparison of iron content at different height positions of the mixed melt in Examples 1-5 From Table 1, the iron content at different altitudes and Figure 1 SEM results showed that there was a relatively large amount of iron phase at the top and a high iron content, while no typical needle-like β-Fe phase or blocky iron phase aggregation was observed at the bottom and the iron content was almost zero, confirming that the process has an excellent effect on promoting the flotation of iron phase.

[0087] It should be noted that the iron phase in this process exists in the form of α-Fe. The top is an iron-rich region with iron phase sizes almost all ≥30μm; while the maximum size of the iron phase in the lower and bottom clean regions is less than 30μm.

[0088] Analysis example 2 The pure aluminum-silicon alloys obtained after zinc volatilization and condensation in Examples 6 and 7 were subjected to ICP analysis to determine the Fe and Zn content. The results are shown in Table 2. Further samples were then taken for scanning electron microscopy (SEM) observation. Figure 2 As shown.

[0089] Table 2. Comparison of iron and zinc content at different locations in the pure aluminum-silicon alloys of Examples 6-7 From the iron and zinc content at different locations in Table 2 and Figure 2 SEM results show that vacuum zinc volatilization-condensation separation can reduce the added zinc content to an extremely low level. The residual zinc content in the obtained pure aluminum-silicon alloy meets the alloy requirements, and the recovered zinc can be directly recycled.

[0090] Comparative Example 1 Ingredients: 187.5g aluminum-silicon alloy and 3.45g Al-10Fe were mixed for composition adjustment. The mass ratio of aluminum to silicon to iron was 92.7:7:0.3; no additional manganese was added.

[0091] S1. Dry 187.5g of aluminum-silicon alloy and 3.45g of Al-10Fe. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly.

[0092] S2. Adjust the temperature of the mixed aluminum melt to 650℃, then add 285.3g of metallic zinc to the mixed aluminum melt, melt it again and stir for 5 minutes to obtain a uniform aluminum-zinc melt; wherein, the mass ratio of mixed aluminum melt to metallic zinc in the mixed aluminum-zinc melt is 4:6.

[0093] S3. Adjust the temperature of the mixed aluminum-zinc melt to 600℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed aluminum-zinc melt is consistent. Then, hold at 600℃ for 1 hour, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0094] Comparative Example 2 Compared to Example 5, the other conditions in this comparative example remain unchanged, except that the addition of metallic zinc in step S2 is omitted.

[0095] Ingredients: Mix 189g of aluminum-silicon alloy, 3.45g of Al-10Fe, and 6.3g of Al-10Mn to adjust the composition. The mass ratio of aluminum to silicon to manganese to iron is 92.4:7:0.3:0.3; the molar ratio of manganese to iron is 1.83:1.

[0096] S1. Dry 189g of aluminum-silicon alloy, 3.45g of Al-10Fe, and 6.3g of Al-10Mn. Preheat the aluminum alloy melting furnace to 700℃. Put the dried aluminum material into the aluminum alloy melting furnace and heat it until the alloy is completely melted. Then, slowly stir the mixed melt for 5 minutes to ensure that the aluminum materials of different compositions are mixed evenly.

[0097] S2. Adjust the temperature of the mixed aluminum melt to 650°C, then add no zinc to the mixed aluminum melt, and perform melting and stirring for 5 minutes.

[0098] S3. Adjust the temperature of the mixed melt to 600℃ and stir for 15 minutes to ensure that the composition of all parts of the mixed melt is consistent. Then hold at 600℃ for 1 hour, and then open the lid and cool down to room temperature with the furnace to obtain aluminum ingots.

[0099] Analysis example 3 Samples (1-6) were taken sequentially from top to bottom of the alloy ingots in Comparative Examples 1 and 2 at equal intervals, and the Fe content was tested. The results are compared in Table 3. Scanning electron microscopy (SEM) was used to observe the top and bottom samples of each comparative alloy ingot. Figure 3 As shown.

[0100] Table 3. Comparison of iron content at different height positions in the mixed melts of Comparative Examples 1 and 2 From Table 3, Figure 3 visible: In Comparative Example 1, without the addition of manganese to the melt, although the iron phase floated slightly to the surface, the iron content at position 1 at the very top was significantly lower than that at position 2, indicating that not adding manganese would worsen the iron phase floating process. Furthermore, without the addition of manganese, the iron phase was mostly needle-like β-Fe, which is highly detrimental to the alloy's properties.

[0101] In Comparative Example 2, without the addition of zinc to the melt, the iron content at different heights was not significantly different, all around 0.3 wt%, indicating that the addition of zinc was the key factor that caused the iron phase to float.

[0102] The above technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made under the technical concept of the present invention using the contents of the present invention specification and drawings, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A method for deep removal of impurity iron from low-iron recycled aluminum-silicon alloy materials, characterized in that, Includes the following steps: Low-iron recycled aluminum-silicon alloy is mixed and melted with manganese-containing compounds to obtain a mixed aluminum melt; Add metallic zinc to the mixed aluminum melt to form an aluminum-zinc melt; The aluminum-zinc melt is cooled to 570℃~620℃ and held for heat treatment to allow the iron-rich phase to float to the surface of the melt. Then, the melt is cooled to solidify and obtain aluminum ingots. The lower part of the aluminum ingot is taken and subjected to vacuum zinc volatilization-condensation separation to obtain a pure aluminum-silicon alloy.

2. The method according to claim 1, characterized in that, In the mixed aluminum melt, the molar ratio of manganese to iron is (1~3):1; In the aluminum-zinc melt, the mass ratio of the mixed aluminum melt to metallic zinc is 3:(3~7).

3. The method according to claim 1, characterized in that, The low-iron recycled aluminum-silicon alloy contains 4-12 wt.% silicon and 0.15-1.0 wt.% iron.

4. The method according to claim 1, characterized in that, The manganese-containing compound includes an aluminum-manganese master alloy; the mass percentage of manganese in the aluminum-manganese master alloy is 10-20%.

5. The method according to claim 1, characterized in that, The temperature at which the low-iron recycled aluminum-silicon alloy is mixed and melted with the manganese-containing compound is ≥700℃; The temperature at which zinc is added to the mixed aluminum melt for melting is 630~700℃.

6. The method according to claim 1, characterized in that, The method of cooling the aluminum-zinc melt to 570°C~620°C includes slow cooling, with a slow cooling rate of 50~100°C / h; The heat preservation treatment lasts for 30 to 180 minutes; before the heat preservation treatment, a stirring treatment is also included, which lasts for 15 to 20 minutes.

7. The method according to claim 1, characterized in that, The cooling process includes rapid cooling, with a rapid cooling rate of ≥150℃ / h.

8. The method according to claim 1, characterized in that, The method for removing the lower part of the aluminum ingot is as follows: the top area of ​​the aluminum ingot is removed, and the remaining area is subjected to vacuum zinc volatilization-condensation separation; the top area accounts for more than 10% of the total height of the aluminum ingot.

9. The method according to claim 1, characterized in that, The conditions for vacuum zinc volatilization-condensation separation are as follows: the temperature of the reaction zone is 880~920℃; the reaction zone is evacuated to a vacuum state before heating; and the distillation separation time after the reaction zone reaches 880~920℃ is 1.5~4h.

10. A pure aluminum-silicon alloy with deep removal of impurity iron, prepared by the method according to any one of claims 1 to 9, characterized in that, The pure aluminum-silicon alloy contains less than 0.12 wt.% iron and less than 0.01 wt.% zinc. In the pure aluminum-silicon alloy, the iron phase is in the form of non-needle-shaped blocks or granules, and the maximum size of the iron phase is ≤30μm.